2016
DOI: 10.1039/c6nr03695c
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced 2-way electron transfer in composites of metal nanoclusters and semiconductor quantum dots

Abstract: In order to explore the potential of nanocomposites comprising semiconductor quantum dots (QDs) and metal nanoclusters (NCs) in photovoltaic and catalytic applications, the interaction between CdTe QDs and gold NCs, Au10 and Au25, stabilized by histidine, bovine serum albumin (BSA) and glutathione, is studied by an ultrafast transient absorption (TA) technique. Temporal and spectral studies of the transients reveal photoinduced 2-way electron transfer between the two constituents of the nanocomposites, where A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…As the bleach amplitude is a measure of the number of carriers relaxing to the band edge, by monitoring this quantity one can determine whether the carriers are extracted and to what extent. , A lower peak bleach amplitude in CsPbBr 3 -MTH NCs (Figure ) compared to CsPbBr 3 under identical conditions clearly indicates transfer of the hot holes to MTH. The dependence of the HC transfer efficiency on the excitation energy is depicted in Figure .…”
mentioning
confidence: 99%
“…As the bleach amplitude is a measure of the number of carriers relaxing to the band edge, by monitoring this quantity one can determine whether the carriers are extracted and to what extent. , A lower peak bleach amplitude in CsPbBr 3 -MTH NCs (Figure ) compared to CsPbBr 3 under identical conditions clearly indicates transfer of the hot holes to MTH. The dependence of the HC transfer efficiency on the excitation energy is depicted in Figure .…”
mentioning
confidence: 99%
“…The behavior of metal nanoclusters (NCs) on photoexcitation has been the center of scientific interest for a few decades now. Photoexcited metal NCs are used in water splitting, electron–phonon coupling, , photoinduced electron transfer (PET), batteries, and solar cells. It was observed that the application of copper NCs (Cu NCs) is comparatively much less in this context. Although Cu NCs possess good fluorescence quantum yield (QY) and capability to be applied in biology, still, the principal handicap is their stability and shelf-life since Cu(0)/Cu­(I) undergoes aerial oxidation to form Cu­(II) .…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, chiral emitting gold nanoclusters, in which the two enantiomers of histidine (His) have been used as both reducing agent and protecting ligands, have been easily synthesized by a one-step approach [18,19]. The presence of suitable ligands bearing –NH 2 , –COOH, or polymerizable substituents open the way to further functionalization of NCs for applications in sensing, bioimaging, and energy transfer [20,21,22]. A central focus throughout materials research is control of the organization of the clusters on nanostructured surfaces, as well as understanding of the growth mechanisms at an atomic scale in order to obtain well defined and uniform architectures [23].…”
Section: Introductionmentioning
confidence: 99%